Anthracene as a sensitiser for near-infrared luminescence in complexes of Nd(III), Er(III) and Yb(III): an unexpected sensitisation mechanism based on electron transfer. - Lazarides, T; Alamiry, M; Adams, H; Pope, S; Faulkner, S; Weinstein, J; Ward, MD (2007)
The ligand L(1), which contains a chelating 2-(2-pyridyl)benzimidazole (PB) unit with a pendant anthacenyl group An connected via a methylene spacer, (L(1) = PB-An), was used to prepare the 8-coordinate lanthanide(III) complexes [Ln(hfac)(3)(L(1))] (Ln = Nd, Gd, Er, Yb) which have been structurally characterised and all have a square antiprismatic N(2)O(6) coordination geometry. Whereas free L(1) displays typical anthracene-based fluorescence, this fluorescence is completely quenched in its complexes. The An group in L(1) acts as an antenna unit: in the complexes [Ln(hfac)(3)(L(1))] (Ln = Nd, Er, Yb) selective excitation of the anthracene results in sensitised near-infrared luminescence from the lanthanide centres with concomitant quenching of An fluorescence. Surprisingly, the anthracene fluorescence is also quenched even in the Gd(III) complex and in its Zn(II) adduct in which quenching via energy transfer to the metal centre is not possible. It is proposed that the quenching of anthracene fluorescence in coordinated L(1) arises due to intra-ligand photoinduced electron-transfer from the excited anthracene chromophore (1)An* to the coordinated PB unit generating a short-lived charge-separated state [An(.+)-PB(.-)] which collapses by back electron-transfer to give (3)An*. This electron-transfer step is only possible upon coordination of L(1) to the metal centre, which strongly increases the electron acceptor capability of the PB unit, such that (1)An* --> PB PET is endoergonic in free L(1) but exergonic in its complexes. Thus, rather than a conventional set of steps ((1)An* -->(3)An* --> Ln), the sensitization mechanism now includes (1)An* --> PB photoinduced electron transfer to generate charge-separated [An(.+)-PB(.-)], then back electron-transfer to generate (3)An* which finally sensitises the Ln(III) centre via energy transfer. The presence of (3)An* in L(1) and its complexes is confirmed by nanosecond transient absorption studies, which have also shown that the (3)An* lifetime in the Nd(III) complex matches the rise time of Nd-centred near-infrared emission, confirming that the final step of the sequence is (3)An* --> Ln(III) energy-transfer.